Determinants of unmet needs for mental health services amongst adolescents in Shiraz, Iran: a cross-sectional study - Joulaei, Hassan; Fatemi, Maryam; Joulaei, Razieh; Heydari, Mohammad Reza; Pourmontaseri, Ahmad Reza; Foroozanfar, Zohre (Frontiers in Public Health, 2024)
Background: Mental disorders are increasingly prevalent among adolescents, yet remain unmet.There are a variety of reasons for unmet mental health needs, including attitudinal and structural barriers. Accordingly, we investigated perceived mental health needs, using mental health services, and their barriers in adolescents.This cross-sectional study was conducted in 2022 in Shiraz, Iran. Demographic characteristics, the Adolescent Unmet Needs Checklist, and the Young Schema Questionnaire were administered to 348 adolescents aged 13-19 years. Adolescents were classified as having no needs, fully met needs, partially met needs, or wholly unmet needs. Logistic regression analysis was used to determine factors associated with perceived unmet need and refer participants to healthcare centers.Results: 193 (55.5%) adolescents reported perceived need for mental healthcare out of whom21.6% reported fully and 21.6% partially unmet needs. Noticeably, only 12.4% of needy participants reported met need. "Reluctance to seek mental healthcare" and "asked but not receiving help" were common barriers to using the services.The present study reveals unmet mental healthcare needs as a significant public health concern among the adolescents. To address this significant concern, reorientation of primary care, removing economic barriers from mental healthcare services, and improving health literacy in the community are recommended.